2018
DOI: 10.1186/s13019-018-0708-7
|View full text |Cite
|
Sign up to set email alerts
|

Modified double patch repair with infarct exclusion technique for ventricular septal perforation: a case study

Abstract: BackgroundVentricular septal perforation (VSP) after acute myocardial infarction (AMI) is accompanied by the worsening of rapid hemodynamics, resulting in a poor prognosis. In our department, infarct lesions are preoperatively detected with electrocardiogram (ECG)-synchronized contrast computed tomography, and the scope of approach and exclusion is determined. Furthermore, to effectively prevent a residual shunt, modified double patch repair and infarct exclusion techniques were used in combination to preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The surgery primarily employs either the David technique, which involves infarct exclusion, or the Daggett technique, which utilizes a single or double patch [4]. Several studies have indicated that the use of the infarct exclusion technique with a double patch yields superior outcomes [6,9,10]. Recently, transcatheter approaches using a VSP occluder have gained popularity due to their less invasive nature.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery primarily employs either the David technique, which involves infarct exclusion, or the Daggett technique, which utilizes a single or double patch [4]. Several studies have indicated that the use of the infarct exclusion technique with a double patch yields superior outcomes [6,9,10]. Recently, transcatheter approaches using a VSP occluder have gained popularity due to their less invasive nature.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery primarily employs either the David technique, which involves infarct exclusion, or the Daggett technique, which utilizes a single or double patch (5). Several studies have indicated that the use of the infarct exclusion technique with a double patch yields superior outcomes (7,10,11). Recently, transcatheter approaches using a VSP occluder have gained popularity due to their less invasive nature.…”
Section: Discussionmentioning
confidence: 99%